Selection on space use in a polymorphic lizard - Olsson, M; Wapstra, E; Healey, M; Schwartz, T; Uller, T (2008)
Background: Polymorphism within the same species, population, and sex is an interesting problem for the evolutionary biologist, since differences in fitness between the morphs have to cancel out over evolutionary time, otherwise morphs of lower fitness would become extinct. One way this may be achieved is through the adoption of different morph-specific reproductive strategies, allowing morphs to become conditional specialists in space (co-existing) or in time (and cycle in frequency). In either case, we expect selection to be disruptive on data pooled across morphs. Question: In the annual Australian painted dragon lizard (Ctenophorus pictus; less than 10% survive to a second year), red males dominate yellow males in staged contests, and yellow males (sneakers) are superior in sperm competition trials. Here, we ask whether there is ongoing disruptive selection for red males to defend well-defined, smaller territories (dominants) and for yellow males to have larger, more loosely defined territories (sneakers). Methods: We monitored free-ranging lizards in a natural population, assigned paternity using microsatellites, and calculated selection coefficients to assess ongoing sexual directional and quadratic selection on territory size. Results and conclusions: Despite the different reproductive strategies, selection on space use in a natural population was not disruptive in either of the two years studied. Instead, there was no difference in territory size between morphs, and in one year there was ongoing directional (positive) and quadratic (stabilizing) selection on territory size applying across both morphs. Thus, divergence of male reproductive strategies in C. pictus does not seem to be related to differences in space use.